The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2013
DOI: 10.1111/jcpt.12092
|View full text |Cite
|
Sign up to set email alerts
|

Predictive performance of reported population pharmacokinetic models of vancomycin in Chinese adult patients

Abstract: SUMMARYWhat is known and objective: There are numerous studies on population pharmacokinetics of vancomycin in adult patients. However, there is no such research for Chinese adult patients. This study was conducted to evaluate the predictive performance of reported population pharmacokinetic models of vancomycin in Chinese adult patients and to identify some models appropriate for our population. Methods: A literature search was conducted in PubMed to obtain the population pharmacokinetic models of vancomycin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 29 publications
3
20
0
Order By: Relevance
“…Similar findings were reported in a previous study that if only a single sample was utilized, Bayesian predicted concentrations were less accurate when obtained using the first ('oldest') observed concentration compared with the most recent observed vancomycin concentration (14). By contrast, in the general patient population, it was reported that taking more TDM data into account did improve the performance of Bayesian forecasting for vancomycin (15).…”
Section: Discussionsupporting
confidence: 87%
“…Similar findings were reported in a previous study that if only a single sample was utilized, Bayesian predicted concentrations were less accurate when obtained using the first ('oldest') observed concentration compared with the most recent observed vancomycin concentration (14). By contrast, in the general patient population, it was reported that taking more TDM data into account did improve the performance of Bayesian forecasting for vancomycin (15).…”
Section: Discussionsupporting
confidence: 87%
“…It is known that external validation of existing models with own data does not always result in good performance and usefulness of the existing models (18).…”
Section: Discussionmentioning
confidence: 99%
“…The maximum a posteriori Bayesian estimation method has already been used to support vancomycin dosing decisions in adults (Deng et al, 2013 ; Jacqz-Aigrain et al, 2015 ) and children (Le et al, 2014 ). To obtain accurate estimation with this method for individualized therapy, it is crucial that reliable population pharmacokinetic characteristics are known for the target patients.…”
Section: Introductionmentioning
confidence: 99%